(untitled) (Baghdad Science Journal, 2007)
A series of experiments were conducted for the first time in Iraq to evaluate the efficiency of five plant leaves extracts (Ibicella lutea, Nerium oleander, Clerodendron inerme, Allium cepa and Eucalyptus spp.) in treating the common carp (Cyprinus carpio) infected with monogenetic trematodes of genera Dactylogyrus. Five different concentrations of such extracts were used to bathe fishes for 5,10,15,20 and 25 minutes. A concentration of 15% A. cepa for 25 minutes of bath exposure was affective in trematode eradication. Extracts of both Eucalyptus and N. oleander at a concentration of 10% each were also affective for ten minutes exposure. Extracts of C. inerme had no any effect on such parasites. On the otherhand, extracts of 1. hitea caused a serious damage to treated fishes when used at different concentrations ans at different periods od exposure.